MATHEMATICAL MODEL OF THE METHOD OF PROTECTING CORPORATE NETWORK INFORMATION RESOURCES USING PROBABILITY TRUST CRITERIA - CHESHUN, VIKTOR; MALYTSKYI, TARAS; OLEKSIUK, DMYTRO; CHESHUN, DMYTRO (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Abstract. The article is devoted to the presentation of a mathematical model of the method of protecting information resources of the corporate network from unauthorized access using probabilistic trust criteria. According to the results of the analysis of the tasks assigned to the method, the conceptual mathematical model of the method of protecting information resources of the corporate network is classified as a probabilistic statistical model of access control systems based on the concept (criteria) of trust. The mathematical model of the method is focused on the statistical analysis of the interaction between various subjects (users) and objects (information resources) in the information environment of the corporate network and provides a toolkit for determining the degree of trust in subjects of information relations in the corporate network from the point of view of information security. Plural of objects and subjects of information relations are identified in the model. A binary access matrix was selected as the main element for managing access to information resources of the corporate network, the rules for its formation are detailed. A formula for calculating the probabilistic criterion of trust in the user based on statistical data about his actions in the network is also proposed. The principles of using the data of the vector of trust criteria and the vector of limit restrictions for making changes to the user’s access rights are defined. The change of access rights is implemented in real time through the adjustment of the access matrix taking into account the decrease in the criterion of trust in the user according to the statistics of his work. The principles of applying the model are demonstrated by the structural and logical diagram of the relationship between the elements of the mathematical model in the implementation of the method.